Attitudinal Meaning Analysis Based on Linguistic Corpus in Parenting Text Translation - Riris Mutiara Simamora (Balai Bahasa Sulawesi Selatan, 2024)
The depiction of language used in parenting books becomes important to study because parenting books are one of the information media used by parents to obtain guidance, knowledge, and direction in child rearing. This research is aims to examine how parents and children are portrayed in parenting books by assessing the expressions that appear in the text, both in the Source Text (ST) and the Target Text (TT). The research method used is qualitative descriptive using the appraisal theory by Martin White (2005) with the assistance of AnCont 3.5.9 (Windows) 2020 Corpus Linguistics. The data source used is a parenting book by Philippa Perry, published by Penguin Life titled